Desorption characteristics and kinetic parameters determination of molecular sieve by thermogravimetric analysis/differential thermogravimetric analysis technique - Yalou Guo; Hui Zhang; Yingshu Liu (Adsorption Science & Technology)
The kinetics of the thermal desorption of CO 2 adsorbed on zeolite 13X were obtained using a differential thermogravimetric analyser under two different carrier gas conditions. The varying heating rates were set as 8, 12, 16, and 20 K min −1 , respectively. The desorption activation energy of the physisorption sites for this experiment evaluated by an integral method without prediction of the reaction order ranged from 12.15 to 14.12 kJ mol −1 (CO 2 as the carrier gas) and 43.32 to 50.42 kJ mol −1 (Ar as the carrier gas), respectively. The desorption activation energy of the chemisorption sites ranged from 57.95 to 58.53 kJ mol −1 (CO 2 as the carrier gas) and 74.02 to 79.92 kJ mol −1 (Ar as the carrier gas), respectively.